Family History of Hypertension and Hypertension’s Associated Risk Factors from Diet among the Saudi Population (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Hypertension (HTN) is defined as a clinic (office) systolic blood pressure ≥140 mm Hg and/or diastolicblood pressure ≥90 mm Hg. It is common, but if left untreated, it can be serious. HTN is classified as primary or secondary.High blood pressure is a disorder that damages blood vessels by forcing blood against the walls of the arteries. Thecirculatory system will be under greater stress, which raises the chance of cardiac conditions such as stroke, aneurysm,and congestive heart failure, as well as other conditions including renal issues, retinal hemorrhage, metabolic syndrome,and dementia. There has been a growing worry worldwide over the rise in teenage and young adult HTN cases, whichgo undiagnosed due to insufficient screening in that age group. We are conducting this study due to insufficient numberof researches related to our topic, especially in Saudi Arabia. Objective: The study aimed to assess the respondents’family history of HTN and its associated risk factors from dietary triggers among the Saudi population. Materials andMethods: This was a cross-sectional study. This study, which conducted from July 2024 to February 2025, uses an onlinequestionnaire to assess the prevalence of HTN and its associated risk factors (dietary among patients in Saudi Arabia). Thestudy plans to recruit participants through an online questionnaire. The inclusion criteria for this study were as follows:All Saudi males and females over 18 years. Non-Saudis,